Analisis Pelanggaran Ketenagakerjaan Studi Kasus Penahanan Ijazah UD Sentoso Seal - Intan Putri Aditria; Yusuf Priya Maulana; Riska Dwi Laluna; Muhabah Najma Salsa Maulida; Fachri Ali Mukti; Bunga Novita Suryani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The withholding of diplomas by companies as a form of control over workers is a practice that occurs quite often in Indonesia, but rarely receives serious attention. The case at UD Sentoso Seal Surabaya shows how dozens of workers lost access to their important documents, which should have been a personal right and a condition of job mobility. This article discusses the phenomenon as a form of labor and human rights violation. Using a case study approach and legal review, it is found that the withholding of these certificates has a direct impact on the economic, educational and psychological rights of the workers. In addition, this practice creates inequality in industrial relations and hampers efforts to create a fair and humane work climate. The government has taken a number of steps such as issuing regulations, sealing warehouses, and reissuing certificates, but these efforts have not touched the root of the problem. This study emphasizes the importance of reforming the labor inspection system and empowering workers to understand and demand their rights. Protecting workers' dignity is not just a legal obligation, but a moral call to ensure that every individual can work in a fair, free and dignified environment.